Bringing the State Back In: Energy and National Security in Contemporary International Relations - Hadiwinata, Bob Sugeng (Global: Jurnal Politik Internasional, 2006)
This paper attempts to discuss the resurgence of the state as an important actor in dealing with energy crisis. The shortfall of oil supply and the steady increase of oil consumption in the past fews years—which resulted in sharp increase of oil prices—have rendered the state responsible for formulating and implementing energy policies to ensure national security. The discussion will be divided into three main sections. The first section will analyze the resurgence of states as prime actor in international relations. After being sidelined for sometime (due to the transformation of international issues from traditional strategic-military concern into economic and humanitarian concern), the state regained currency in the wake of terrorist and energy threats. The second section will discuss the current energy security problem and how it affects nation-states. The final section will analyze U.S. response to current energy crisis. Attention will be put on how U.S. government produce and implement energy policies to ensure its national security.